2023
DOI: 10.3390/agriculture13071319
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Different Environments on Productive Performance, Welfare, and the Health of Muscovy Ducks during the Summer Season

Abstract: The objective of this research was to evaluate the influence of the housing system (deep litter [DL] vs. deep litter with swimming pond [DLSP]) on productive performance, carcass traits, body temperature, blood profile, and the element composition of the femur and tibia in Muscovy ducks. At 5 weeks of age, sexed ducklings (264) were divided into 4 equal groups according to housing system and gender (drakes vs. ducks). The groups were as follows: 66 drakes/DL, 66 drakes/DLSP, 66 ducks/DL, and 66 ducks/DLSP. Eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In addition to nutritional factors, the housing system can influence productive performance, carcass traits, and bone composition in ducks. Krunt et al [19] revealed that ducks reared on deep litter with access to a swimming pond had a higher live weight and better feed conversion ratio but a lower proportion of breast in the carcass structure than ducks maintained on deep litter without access to a pond. Housing conditions did not affect the fracture toughness of the fowl tibia and femur; however, ducks that had access to the pond had more Ca and Mg in the tibia and more Mg in the femur.…”
mentioning
confidence: 99%
“…In addition to nutritional factors, the housing system can influence productive performance, carcass traits, and bone composition in ducks. Krunt et al [19] revealed that ducks reared on deep litter with access to a swimming pond had a higher live weight and better feed conversion ratio but a lower proportion of breast in the carcass structure than ducks maintained on deep litter without access to a pond. Housing conditions did not affect the fracture toughness of the fowl tibia and femur; however, ducks that had access to the pond had more Ca and Mg in the tibia and more Mg in the femur.…”
mentioning
confidence: 99%